The commitment of rhetorical questions - Shigeru Miyagawa (Glossa, 2024)
Rhetorical questions have received a detailed treatment in semantic studies that defined them in terms of common ground updating, assertion and lack of information seeking. How these semantic traits interact with the syntactic derivation of a rhetorical question has been less debated in the literature (with some notable exceptions). This paper adopts the findings of the semantic studies and considers them from a syntactic perspective: to what degree does syntax contribute to the interpretation of an interrogative clause as a rhetorical question? The paper focuses on data where the switch from a heuristic to a rhetorical reading of interrogatives is forced by the insertion of certain lexical items, and analyzes these items within a framework that maps conversational pragmatics to syntax. In particular, the proposal is that the interaction of the question clause typing feature with an evidential feature in the Commitment Phrase (i.e., the projection that relates speaker/addressee to the proposition) has the effect of an assertion that overrides the addressee-orientedness of the interrogative clause.